Urban food waste for soil amendment? Analysis and characterisation of waste-based compost for soil fertility management in agroecological horticultural production systems in the city of Rosario, Argentina - Terrile, R.; Martinez, N.; Paz, N.; Brunotto, F.; Costa, M.; Budai, N.; Ruiz, C.; Rizzi, M.; Invernizzi, M.; Scarpeci, T.; Piacentini, R. D.; Winter, K.; et al. (Frontiers in Sustainable Food Systems, 2024)
Urban and peri-urban lands can be an important source of food production for localised and sustainable food systems, however, their soils can be of poor quality, degraded or damaged by anthropic activities, and little is known about their suitability or safety. This paper aims to contribute to this knowledge gap by assessing the soil remediation capacity and qualities of different types of compost made from urban and peri-urban organic wastes for agroecological food production. Prepared over the course of 2021, and used in 2022 for food growing, five different composts were observed and analysed, in two different farms in the city of Rosario, Argentina. Four raw materials generated largely by local industries were used to make the composts: chicken manure, rumen (cow’s stomachs), brewer’s bagasse (byproducts of the beer industry) and urban leaves collected from the municipality waste collection. These were mixed in different proportions (all reaching the 20–30 C/N ratio, typical of quality compost) to produce viable growing substrates where radishes and lettuces were grown. The aim of the study was to assess the possibility, quality and limitations to use locally available organic inputs for soil fertility management in agroecological farming, in the context of urbanisation and to assess pathways to develop closed-cycle agroecological agriculture at metropolitan level. Natural manure substrates (raw and composted) were analysed, as well as crops grown and fertilised with each of the substrates. The attributes and limiting factors of each substrate and their response to local soil conditions were compared and physicochemical, biochemical, and microbiological analyses were performed, including among others, the study of microbial biomass, biological activity, biophytotoxicity, pH, aerobic heterotrophs, nitrogen fixation, and the presence of antibiotics, agrochemicals and heavy metals. The results of the analyses show that all the composted materials improved the physical, chemical and biological properties. However, in some cases, pollutants were present even after composting. Analysis carried out on the vegetables generally indicate undetectable levels or levels below the admissible limits, demonstrating the filtering capacity of the different composts and the soil.